Tingkat Motivasi Latihan Ukm Panahan Teknokrat Selama Pandemi Covid - Ichsanudin Ichsanudin; Aditya Gumantan (Universitas Teknokrat Indonesia, 2020)
Training activity is related to an achievement which cannot be separated from many factors and one of them is training motivation. The level of motivation possessed by the members of the Archery UKM at the University of Teknorat Indonesia has not been clearly described during the Covid-19 pandemic. With the aim of this study is to determine the level of motivation for training in Archery UKM This research is a descriptive study using the analytical survey method. The subject of this research is the Archery UKM of Technorat University of Indonesia, with a total of 15 members. The data collection technique in this study used an instrument in the form of a questionnaire. The data analysis technique used in this research is descriptive statistical analysis with proportions. The results showed that the level of motivation to exercise was 87.77%, which was divided into 53.33% intrinsic factors and 46.66% extrinsic factors. Likewise, the results of training motivation during the Covid-19 pandemic for Archery UKM Members can be classified as high.